DISCUSSIONS OF POLITICAL ISSUES AT FOREIGN LANGUAGES’ CLASSES FOR UNIVERSITY LEVEL STUDENTS - Iljina, Svetlana; Laganovska, Karīne; Opincāne, Mārīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Discussion is a methodological instrument, which helps to perfect students’ communicative competence and the central process through which students can be encouraged interact with one another, their academics, and the information sources. A foreign language academic encourages discussion using newspaper headlines. The topicality of the headlines contain indirect impulses, which encourages a reader (a student) to develop and express his/her own opinion. Migration issues have become topical and up-to-date recently. Higher education also is a sphere of life, which is concerned with this topic. The topic is also in the focus of students and academics’ attention at Rezekne Academy of Technologies and is used successfully at foreign languages’ classes. The aim of the paper is to demonstrate methodological approaches how to develop students’ discussion skills on political issues through the acquisition of migration terminology using newspaper headlines and using of them in discussions on the migration issues.Communicative, discourse analysis content and critical analysis methods were used in the research. Vocabulary is crucial in learning and teaching for specific purposes. Three C’s (conveying meaning, checking, and consolidation) approach has been used in acquisition of new vocabulary at foreign language classes. Foreign languages for specific purposes concentrate more on language in context than on teaching grammar and language structures.